2021
DOI: 10.1371/journal.pone.0252244
|View full text |Cite|
|
Sign up to set email alerts
|

Deployment optimization of multi-stage investment portfolio service and hybrid intelligent algorithm under edge computing

Abstract: The purposes are to improve the server deployment capability under Mobile Edge Computing (MEC), reduce the time delay and energy consumption of terminals during task execution, and improve user service quality. After the server deployment problems under traditional edge computing are analyzed and researched, a task resource allocation model based on multi-stage is proposed to solve the communication problem between different supporting devices. This model establishes a combined task resource allocation and tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Image examinations include ultrasound scanning, computed tomography (CT), magnetic resonance imaging, and endoscopic examination. Among them, CT images have a relatively high resolution and do little harm to the human body and are of certain value in early diagnoses of pancreatic cancer; so, they are widely used in clinical practice [ 10 ]. However, doctors' judgments and analyses of patient images are greatly influenced by their subjective factors.…”
Section: Introductionmentioning
confidence: 99%
“…Image examinations include ultrasound scanning, computed tomography (CT), magnetic resonance imaging, and endoscopic examination. Among them, CT images have a relatively high resolution and do little harm to the human body and are of certain value in early diagnoses of pancreatic cancer; so, they are widely used in clinical practice [ 10 ]. However, doctors' judgments and analyses of patient images are greatly influenced by their subjective factors.…”
Section: Introductionmentioning
confidence: 99%
“…The side effects of opiates are reduced, and patients' analgesic needs can be met [ 14 ]. The drugs commonly adopted in CEA are local anesthetics and opiates, which show poor analgesic effects and cause nausea, emesis, drug dependence, and other side effects [ 15 ]. Dexmedetomidine (Dex) is a highly selective α 2-adrenergic receptor agonist, which can act directly on peripheral α 2 receptors, reduce the release of norepinephrine, and further show sedative and analgesic effects [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic floor rehabilitation training is a relatively rapidly developing rehabilitation field in recent years. It is a rehabilitation training method to promote the recovery of nerves and muscles injured during pregnancy and delivery, which can improve the long-term pelvic floor conditions, while reducing the chance of FPFD due to changes in anatomical structure and age [ 7 10 ]. Studies have shown that pelvic floor training during pregnancy can reduce the incidence of FPFD in primipara 3 months after delivery, and postpartum rehabilitation can significantly reduce the incidence of FPFD 6-12 months after delivery [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%